Incidence, etiology, sociodemographic and clinical characterization of acute respiratory failure in pediatric patients at a high-altitude city: A multicenter cohort study - Vargas Muñoz, Sarha M.; De Vivero Haddad, Sara; Beltran, Aldo M.; Bonilla Gonzalez, Carolina; Naranjo Vanegas, Melisa; Moreno-Lopez, Sergio; Rueda-Guevara, Paola; Barrera, Pedro; Piñeros, Juan Gabriel; Mejía, Luz Marina; Mesa, María Lucia; Restrepo-Gualteros, Sonia; et al. (Frontiers in Pediatrics, 2022)
Background Acute respiratory failure is a life-threatening medical condition, associated with a variety of conditions and risk factors, including acute respiratory diseases which are a frequent cause of pediatric morbidity and mortality worldwide. In Colombia, the literature related to ARF is scarce. Objective To determine the incidence, causes, and sociodemographic and clinical characteristics of ARF in three hospitals in Bogota, a high-altitude city located in Colombia, during the COVID-19 pandemic. Methods A multicenter prospective cohort study called the FARA cohort was developed between April 2020 – December 2021. Patients older than one month and younger than 18 years with respiratory distress who developed ARF were included. Results 685 patients with respiratory distress were recruited in 21 months. The incidence density of ARF was found to be 41.7 cases per 100 person-year CI 95%, (37.3–47.7). The median age was 4.5 years.. Most of the patients consulted during the first 72 h after the onset of symptoms. Upon admission, 67.2% were potentially unstable. The most frequent pathologies were asthma, bronchiolitis, pneumonia, and sepsis. At admission, 75.6% of the patients required different oxygen delivery systems, 29,5% a low-flow oxygen system, 36,8% a high-flow oxygen system, and 9,28% invasive mechanical ventilation. SARS-COV-2, respiratory syncytial virus, rhinovirus/enterovirus, and adenovirus were the most frequently isolated viral agents. The coinfection cases were scarce. Conclusions This multicenter study, the FARA cohort, developed at 2,600 meters above sea level, shows the first data on incidence, etiology, sociodemographic and clinical characterization in a pediatric population with ARF that also concurs with the COVID-19 pandemic. These results, not only have implications for public health but also contribute to the scientific and epidemiological literature on a disease developed at a high altitude.